Positive Association Between Therapeutic Alliance and Quality of Life in Psychodynamic Psychotherapy, Cognitive Behavior Therapy, and Interpersonal Therapy: The Patient's Perspective - Barbisan, Guilherme Kirsten; de Pieri, Luiza Zamban; Gonçalves, Leonardo; Rebouças, Cinthia Danielle Vasconcelos; da Rocha, Neusa Sica (Frontiers in Psychiatry, 2022)
Background The therapeutic alliance (TA) is considered a common psychotherapeutic factor associated with positive results in psychotherapies. There are no studies relating the TA with quality of life (Qol). Objectives Our objective was to evaluate whether there is an association between the TA and Qol across three different psychotherapies. Methods A cross-sectional study, which included outpatients undergoing individual psychotherapeutic treatment was conducted. When analyzing the total sample, the correlation of the TA with Qol domains did not present statistical significance. When considering only the sample of patients who were undergoing treatment in psychodynamic psychotherapy (PP), there was a statistically significant association between the TA and the psychological domain of Qol (p < 0.05). When using a regression model for adjusting for confounding factors, the association between psychological domain with the TA on the PP patients sample lost significance (p = 0.221). Discussion These findings suggest that the TA seems to be more strongly related to better QoL in PP.